(untitled) (Interdisciplinary Studies Journal, 2024)
There were numerous delicate situations during the pandemic period, which forcibly separated people from their social interactions, and education was no different. Children stopped attending school, and as a result, the initiation of writing in early childhood education experienced certain fragility. The research sought support in legal documents, published articles, and theoretical frameworks, with both quantitative and qualitative approaches. The objectives were to analyze the initiation of the writing process in 4- and 5-year-old children upon returning to in-person classes and to discuss how the initiation of writing occurred for these children during the pandemic in early childhood education. Fourteen children from two CMEIs participated in the research. For data analysis, writing tests were applied. From the collected data, 87% had not yet mastered the initiation of writing after the pandemic. The data analysis shows the need to rethink actions to overcome the shortcomings left by the pandemic.